Metaflammation, NLRP3 Inflammasome Obesity and Metabolic Disease - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: Increasing prevalence of obesity gives rise to many problems associated with multiple morbidities, such as diabetes, hypertension, heart disease, sleep apnea and cancer. The mechanism of obesity is very complex, thus its link to various disease is poorly understood. This review highlights important concepts in our understanding of the pathogenesis of obesity and related complications.CONTENT: Many studies have tried to explore the exciting and puzzling links between metabolic homeostasis and inflammatory responses. A form of subclinical, low-grade systemic inflammation is known to be associated with both obesity and chronic disease. This, later called as